Penggunaan Cover Eye Dan Ear Plug Terhadap Kualitas Tidur Pasien Dengan Stemi - Roni, Roni; Hartati, Sri; Wibowo, Wahyu Dwi Ari (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
The quality of sleep among patients with ST-Elevation Myocardial Infarction (STEMI) in Intensive Care Units (ICU) is often compromised due to various factors, including the high level of medical intervention and external environmental stimuli. This study aimed to assess the impact of non-pharmacological interventions, specifically eye covers and ear plugs, on improving sleep quality in STEMI patients admitted to the ICU. A quasi-experimental pre-post design was used, involving 22 patients in the ICU of Siti Aisyah Hospital, Lubuklinggau, during 2024. The Pittsburgh Sleep Quality Index (PSQI) was used to measure the patients' sleep quality before and after the intervention. The results indicated a significant improvement in sleep quality, with the mean PSQI score decreasing from 14.8182 before the intervention to 9.1818 after the intervention, accompanied by a p-value of 0.000, demonstrating statistical significance. This suggests that the use of eye covers and ear plugs is effective in improving sleep quality in STEMI patients in ICU settings. Further studies with larger samples and diverse patient conditions are recommended to explore the long-term effects of this non-pharmacological intervention.